2019
DOI: 10.1021/acs.jafc.8b06424
|View full text |Cite
|
Sign up to set email alerts
|

Component Profiling in Agricultural Applications Using an Adjustable Acupuncture Needle for Sheath-Flow Probe Electrospray Ionization/Mass Spectrometry

Abstract: In previous work, probe electrospray ionization/mass spectrometry (PESI/MS) and sheath-flow probe electrospray ionization/mass spectrometry (sfPESI/MS) were reported for the rapid and minimally invasive analysis of food. In this work, a modified version of sfPESI will be reported. The sample surface was pricked with an acupuncture needle inserted in the sfPESI probe that protruded from the terminus of the tip by 5 mm. The invasion depth of the needle into the sample was ∼1 mm. After sampling, the needle was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The observed trend is in agreement with the previous work. , Darbyshire and Henry suggested that the concentration change is due to hydrolysis of fructans to free fructose which achieves osmotic adjustment as the base cells expand during bulbing of the onion. In addition, Hex may be functioning in protecting the plant against water deficit as an osmoregulator . To our surprise, the mass spectrum showed a drastic change with #7 → #8.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…The observed trend is in agreement with the previous work. , Darbyshire and Henry suggested that the concentration change is due to hydrolysis of fructans to free fructose which achieves osmotic adjustment as the base cells expand during bulbing of the onion. In addition, Hex may be functioning in protecting the plant against water deficit as an osmoregulator . To our surprise, the mass spectrum showed a drastic change with #7 → #8.…”
Section: Resultsmentioning
confidence: 77%
“…It should be kept in mind that the surface sampling methods such as sfPESI, LESA, , DESI, nanoDESI, SPESI, and Single-probeMS give information mainly on the surface components but not necessarily on the bulk components. For the analysis of components underneath the surface (i.e., bulk analysis), dPESI and ad-sfPESI are more preferable than the surface sampling methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the use of solid substrate for sample delivery and direct electrospray ionisation (ESI) has attracted a lot of attention 18 . Particularly, wooden tip and other probes/needles allow in vivo sampling of living plants for subsequent direct ESI‐MS analysis of raw samples 19–21 . Wooden‐tip ESI‐MS has been successfully demonstrated as an effective, simple, and rapid method for direct analysis of raw samples.…”
Section: Introductionmentioning
confidence: 99%
“…27 However as PESI is only applicable to liquid samples, sheath-ow PESI (sfPESI) was later developed to enable the analysis of non-liquid samples. 28,29 Sheath-ow PESI is a modication of the PESI technique in which the needle is contained within a solvent-lled gel-loading tip with a slight protrusion (0.1 mm) of the needle from the base. When the probe touches the sample surface, the convex liquid at the base of the probe wets the sample and enables analyte extraction from the surface.…”
Section: Introductionmentioning
confidence: 99%